LOS CRISOMELINOS (COLEOPTERA: CHRYSOMELIDAE: CHRYSOMELINAE) DEL ESTADO DE MORELOS - Burgos Solorio, Armando; Anaya Rosales, Socorro (Instituto de Ecología, A.C., 2004)
We describe some biological aspects about the Subfamily Chrysomelinae (common name catarinas) in the state of Morelos; Mexico; A total of 47 species within 8 genera and2 sub-tribes are recorded; The genus Leptinotarsa is the most species rich; Additinal information on host plants; distributions;and feeding habits is provided.